Notes - Mathematics Olympiads - Two Dimensional Geometry
Category : 11th Class
Two Dimensional Geometry (Coordinate and Straight Line)
Key Points to Remember
Let P(x, y) be any point
x\[\to \] abscissa
y\[\to \] ordinate
(a) The distance between two points \[A({{x}_{1}},\,{{y}_{1}})\] & \[B({{x}_{2}},\,{{y}_{2}})\]
\[Ab=\sqrt{{{({{x}_{2}}-{{x}_{1}})}^{2}}+{{({{y}_{2}}-{{y}_{1}})}^{2}}}\]
(b) Distance between the origin 0(0, 0) and the point P(x, y) is OP
\[op=\sqrt{{{x}^{2}}+{{y}^{2}}}\]
e.g.\[A=(5,3)\,\,\,B=(-2,5)\]
\[\therefore \,\,\,AB\]
\[=\sqrt{{{(-2-5)}^{2}}{{(5-3)}^{2}}}=\sqrt{49+4}=\sqrt{53}\]
\[x=\frac{m{{x}_{2}}+n{{x}_{1}}}{m+n},\] \[y=\frac{m{{y}_{2}}+n{{y}_{1}}}{m+n},\]
When P divides AB in the ratio m:n then
\[x=\frac{m{{x}_{2}}-n{{x}_{1}}}{m-n},\] \[y=\frac{m{{y}_{2}}-n{{y}_{1}}}{m-n},\]
When P divides AB in the ratio 1:1 i.e. P is the mid point of AB
\[\therefore \,\,\,\text{P}\equiv \text{(x,y)=}\left( \frac{{{x}_{1}}+{{x}_{2}}}{2},\frac{{{y}_{2}}+{{y}_{1}}}{2} \right)\]
Area of ABC
\[=\frac{1}{2}\{{{x}_{1}}({{y}_{2}}-{{y}_{3}})+{{x}_{2}}({{y}_{3}}-{{y}_{1}})+{{x}_{3}}({{y}_{1}}-{{y}_{2}})\}\]
[Using determinant form]
Note: The rule for writting the area of a quadrilateral is the same as that of a triangle.
Similarly, we can find the area of a polygon of n sides with vertices \[{{A}_{1}}({{x}_{1}},{{y}_{1}}),{{A}_{2}}({{x}_{2}},{{y}_{2}})...{{A}_{n}}({{x}_{n}},{{y}_{n}})\]is
If \[{{a}_{1}}x+{{b}_{1}}y+{{c}_{1}}=0\,\,{{a}_{2}}x+{{b}_{2}}y+{{c}_{2}}=0\] and \[{{a}_{3}}x+{{b}_{3}}y+{{c}_{3}}=0\] are the equation of the triangle. Then the area of the triangle be
Where \[{{c}_{1}},\,{{c}_{2}},\,{{c}_{3}}\] be the co-factor of \[{{c}_{1}},\,{{c}_{2}},\,{{c}_{3}}\] in the determinants:
\[\therefore \,\,\,{{c}_{1}}={{a}_{2}}{{b}_{3}}-{{a}_{3}}{{b}_{2}},\]
\[{{c}_{2}}={{a}_{3}}.{{b}_{1}}-{{a}_{1}}{{b}_{3}}\]
& \[{{c}_{3}}={{a}_{1}}.{{b}_{2}}-{{a}_{2}}{{b}_{1}}.\]
[In determinant form]
Solved Problem
Sol. Let \[A\equiv (a,b+c)\]
\[B\equiv (b,c+a)\]
\[C\equiv (c,a+b),\] be three point.
To show the collinear of the points A, B and C.
Area of \[\Delta ABC\] should be zero.
Now,
[Two columns are identical]
\[=(a+b+c)\times 0=0\]
Hence the points. A, B & C be collinear.
Straight Lines
\[\theta =\frac{{{m}_{1}}-{{m}_{2}}}{1+{{m}_{1}}{{m}_{2}}}\]
Note: If the lines are parallel then
\[\tan \theta =0\]
i.e. \[\frac{{{m}_{1}}-{{m}_{2}}}{1+{{m}_{1}}{{m}_{2}}}=0\]
\[\Rightarrow {{m}_{1}}={{m}_{2}}\]
i.e. if two lines are parallel then their slopes are equal.
\[\tan \theta =\infty \] i.e.
\[\frac{{{m}_{1}}-{{m}_{2}}}{1+{{m}_{1}}{{m}_{2}}}=\infty =\frac{1}{0}\]
\[\Rightarrow 1+{{m}_{1}}.{{m}_{2}}=0\]
\[\Rightarrow {{m}_{1}}.{{m}_{2}}=-1\]
i.e. The product of their slopes is equal to -1.
Sol. Given \[\theta \frac{\pi }{4}\]
& \[{{m}_{1}}=\frac{1}{2}\]
\[\because \] Angle between two lines in tangent form is written as
\[\tan \theta =\left| \frac{{{m}_{1}}-{{m}_{2}}}{1+{{m}_{1}}.{{m}_{2}}} \right|\] (when q is in acute angle) \[\tan \frac{\pi }{4}=\left| \frac{\frac{1}{2}-{{m}_{2}}}{1+\frac{1}{2}{{m}_{2}}} \right|\]
\[\Rightarrow \pm 1=\frac{\frac{1}{2}-{{m}_{2}}}{1+\frac{1}{2}{{m}_{2}}}\]
\[1+\frac{1}{2}{{m}_{2}}=\frac{1}{2}-{{m}_{2}}\] (Taking positive sign)
\[\Rightarrow \frac{1}{2}{{m}_{2}}+{{m}_{2}}=\frac{1}{2}-1=-\frac{1}{2}\]
\[\frac{3}{2}{{m}_{2}}=\frac{-1}{2}\]
\[\therefore \,\,\,\,\,{{m}_{2}}=\frac{-1}{3}\]
Again taking negative sign
\[\therefore \,\,\,\,\frac{\frac{1}{2}-{{m}_{2}}}{1+\frac{1}{2}{{m}_{2}}}=-1\Rightarrow {{m}_{2}}=3\]
Hence the slope of the other line is \[\frac{-1}{3}\] or 3.
Intercept of a line on the axes: Intercept of a line on axis: If a straight line cuts x-axis at A and the y-axis at B then OA & OB is said to be the intercept of the line of x-axis & y-axis respectively.
·
(i) Equation of x-axis is \[y=0\]
(ii) Equation of y-axis is \[x=0\]
(iii) Equation of a line parallel to x-axis be \[y=b\]
(iv) If the line is parallel to x-axis, at the distance, b from it and is an negative side of y axis, then its equation is \[y=-b\]
(v) Equation of a Ine parallel to y-axis is \[x=+a\]
(vi) If the line is parallel to y-axis, at distance a from it and is on the negative side of x-axis, then its equation is \[x=-a\]
Equation of a straight line in various forms
Slope-Intercept form
The equation of a straight line whose slope is m and which cuts an intercept c on the y-axis is given by \[y=mx+c\]
If the line passes through the origin, then \[c=0\] and hence the equation of the line be \[y=mx\]
Solved Problem
Sol. Here \[c=2\] unit
\[\theta =30{}^\circ \]
so, \[m=\tan \theta =\tan 30{}^\circ =\frac{1}{\sqrt{3}}\]
Hence the required equation of straight line be
\[y=mx+c\]
\[y=\frac{1}{\sqrt{3}}x\times 2\]
\[\Rightarrow \,\,\,x-\sqrt{3}y+2\sqrt{3}=0\]
Solved Problem
Sol. Here, given be
\[P\equiv (2,2\sqrt{3}),\theta \equiv 75{}^\circ \]
Slope of straight line, \[m=\tan \theta =\tan 75{}^\circ \]
\[\tan (45{}^\circ +30{}^\circ )=\frac{\tan 45{}^\circ +\tan 30{}^\circ }{1-\tan 45{}^\circ .\tan 30{}^\circ }=\frac{1+\frac{1}{\sqrt{3}}}{1-\frac{1}{\sqrt{3}}\times 1}=\frac{\sqrt{3}+1}{\sqrt{3}-1}=\frac{\sqrt{3}+1}{\sqrt{3}-1}\times \frac{\sqrt{3}+1}{\sqrt{3}-1}\]
\[=\frac{\sqrt{3}+1{{)}^{2}}}{(\sqrt{3{{)}^{2}}-{{(1)}^{2}}}}=\frac{{{(\sqrt{3}+1)}^{2}}+{{1}^{2}}+2\sqrt{3}.1}{3-1}=\frac{4+2\sqrt{3}}{2}=2+\sqrt{3}\]
Hence, the required equation of straight line be
\[y-{{y}_{1}}=m(x-{{x}_{1}})\]
\[y-2\sqrt{3}=(2+\sqrt{3})(x-2)\]
\[\Rightarrow \,\,\,(2+\sqrt{3})x-y+4-2\sqrt{3}\]
\[\Rightarrow \,\,\,(2+\sqrt{3})x-y+4-0\]
Solved Problem
Sol: Slope of AB line \[=\frac{{{y}_{2}}-{{y}_{1}}}{{{x}_{2}}-{{x}_{1}}}=\frac{-4-1}{2-(-1)}=\frac{-5}{3}\]
Thus, the equation of straight line AB be
\[y-{{y}_{1}}=\frac{{{y}_{2}}-{{y}_{1}}}{{{x}_{2}}-{{x}_{1}}}(x-{{x}_{1}})\]
\[\Rightarrow \,\,y-1=\frac{-5}{3}(x+1)\]
\[\Rightarrow \,\,5x+3y-3+5=0\]
\[\Rightarrow \,\,5x+3y+2=0\]
Intercept form
The equation of a straight line which cuts off intercepts a & b. an x-axis & y-axis respectively is written as \[\frac{x}{a}+\frac{y}{b}=1\]
Sol. The equation of straight line in intercept form be
\[\frac{x}{a}+\frac{y}{b}=1\]
since, line cuts off equal intercept on the coordinate axes.
i.e. \[a=b\]
then equation of straight line be \[\frac{x}{a}+\frac{y}{b}=1\]
\[\Rightarrow \,\,\,x+y=a\]
According to the question
straight line passes through (2, 3)
then \[2+3=a\Rightarrow a-5\]
Thus, the required equation of the straight line be
x+y=5=>x+y-5=0
Normal Form (or perpendicular Form):
The equation of a straight line having the length of the perpendicular from the origin is p and the perpendicular makes an angle a with the positive direction of x-axis is written as \[x.\cos \theta =y.\sin \theta =p\]
Note: In normal form of equation of a straight line is always taken as the positive and \[\theta \] is measured from the positive direction of x-axis in anticlockwise direction between 0 and \[2\pi \]
Sol. Here \[p=4\]unit
\[\theta =15\]
Equation of the straight line be
\[x.\cos \theta +y\sin \theta =p\]
\[x.\cos 15{}^\circ +y.\sin 15{}^\circ =4\]
\[\because \] Now, \[\cos 15{}^\circ =\cos (45{}^\circ -30{}^\circ )\]
\[\cos 45{}^\circ .\cos 30{}^\circ +\sin 45{}^\circ .\sin 30{}^\circ \]
\[=\frac{1}{\sqrt{2}}.\frac{\sqrt{3}}{2}+\frac{1}{\sqrt{2}}.\frac{1}{2}=\frac{\sqrt{3}-1}{2\sqrt{2}}\]
Similarly, \[\sin 15{}^\circ =\frac{\sqrt{3}-1}{2\sqrt{2}}\]
Thus, the required equation of the straight line in normal form be
\[x.\frac{\sqrt{3}+1}{2\sqrt{2}}+y.\frac{\sqrt{3}-1}{2\sqrt{2}}=4\]
\[(\sqrt{3}+1)x+(\sqrt{3}-1)y=8\sqrt{2}\]
Parametric Form (or Symmetric form)
The equation of a straight line passing through the point \[({{x}_{1}},\,{{y}_{1}})\] & making an angle a with the positive direction of x-axis is written as \[\frac{x-{{x}_{1}}}{\cos \alpha }=\frac{y-{{y}_{1}}}{\sin \alpha }=r\]
Where r is the distance of the point (x, y) from the point \[({{x}_{1}},\,{{y}_{1}}).\]
Note: If \[Q({{x}_{1}},\,{{y}_{1}})\] be a point on a line AB which makes an angle a with the positive direction of the x-axis, then there will be two points on line AB at distance r from \[Q({{x}_{1}},\,{{y}_{1}})\] and their coordinate will be
\[({{x}_{1}}+r\,\,\cos \theta ,{{y}_{1}}+r\sin \theta )\] and \[({{x}_{1}}-r\,\,\cos \theta ,{{y}_{1}}-r\sin \theta )\]
Reduction (Derived) of the General Equation to the different standard form.
Slope-Intercept form
The general equation of straight line,
\[Ax+By+c=0,\] can be reduced to the form \[y=mx+c\] by expressing y as:
\[y=\frac{-Ax-C}{B}=\left( \frac{-A}{B} \right)x+\left( \frac{-C}{B} \right)\]
i.e. \[m=\frac{-A}{B}\] & \[{{c}_{1}}=\frac{-C}{B}\]
i.e. the slope of the straight line
\[Ax+By+C=0\] be
\[m=\frac{-A}{B}=\frac{-coe\text{ff}icient\,of\,x}{coe\text{ff}icient\,of\,y}\]
& \[y-\operatorname{intercept},{{c}_{1}}=\frac{C}{B}=\frac{-cons\operatorname{tant}\,term}{coe\text{ff}icient\,of\,y}\]
If \[C\ne 0\]
\[\because \] equation of straight line be
\[Ax+By+C=0\]
\[Ax+By=-C\]
Dividing both sides by -C, we have
\[\frac{Ax}{-C}+\frac{By}{-C}=1\]
\[\Rightarrow \frac{x}{\left( \frac{-C}{A} \right)}+\frac{y}{\left( \frac{-C}{B} \right)}=1\]
which is of the form \[\frac{x}{a}+\frac{y}{b}=1\]
\[\therefore \,\,a=\frac{-C}{A}\] & \[b=\frac{-C}{B}\]
lf \[C=0\]
Then the general equation of the straight line \[ax+By+c=0,\] be
i.e. \[Ax+By=0\,\,(\because c=0)\] will be passing through the origin.
1st express it as:
\[Ax+By=-C\] ...... (i)
Case- I: If \[C<0\] or \[-C>0.\]
Dividing both sides of equation (i) by \[\sqrt{{{A}^{2}}+{{B}^{2}}},\] we have \[\frac{Ax}{\sqrt{{{A}^{2}}+{{B}^{2}}}}+\frac{By}{\sqrt{{{A}^{2}}+{{B}^{2}}}}=\frac{-C}{\sqrt{{{A}^{2}}+{{B}^{2}}}}\]
which is of the form \[x.\cos \theta +y.\sin \theta =p\]
where \[\cos \theta =\frac{A}{\sqrt{{{A}^{2}}+{{B}^{2}}}}\]
\[\sin \theta =\frac{B}{\sqrt{{{A}^{2}}+{{B}^{2}}}}\] & \[p=\frac{-C}{\sqrt{{{A}^{2}}+{{B}^{2}}}}\]
Case- II: If \[C>0\]or \[-C<0\]
Then dividing the equation (i) by \[-\sqrt{{{A}^{2}}+{{B}^{2}}},\] we have \[\frac{-Ax}{\sqrt{{{A}^{2}}+{{B}^{2}}}}-\frac{By}{\sqrt{{{A}^{2}}+{{B}^{2}}}}.y=\frac{C}{\sqrt{{{A}^{2}}+{{B}^{2}}}}\]
Which is of the form \[x\cos \theta +y\sin \theta =p\]
Carollary: The length of the perpendicular from the origin on the straight line
\[Ax+By+C=0\] is \[\frac{\left| C \right|}{\sqrt{{{A}^{2}}+{{B}^{2}}}}\]
Tips: 1st of all,
(i) Transpose the constant terms in the R.H.S.
(ii) Then make the constant term positive if it is not already so (this may be done by multiplying throughout by -1 if necessary).
(iii) Divide both sides by
\[\sqrt{{{(coe\text{ff}icient\,\,of\,\,x)}^{2}}+{{(coe\text{ff}icient\,\,of\,\,y)}^{2}}}\]
(iv) Now coefficient of \[x=\cos \theta \]
coefficient of \[y=\sin \theta \]
& R.H.S = p
Condition for two straight line to be coincident, parallel, perpendicular or intersecting.
Two lines \[{{a}_{1}}x+{{b}_{1}}y+{{c}_{1}}=0\]
i.e. They are neither coincident nor parallel.
You need to login to perform this action.
You will be redirected in
3 sec